Optimizing protein yield from growing deer antlers - Nicolás Alegría-Aravena; Nicolás Alegría-Aravena; María-Pilar López-Garrido; Josefa Quiroz-Troncoso; Raquel González-Martos; Marta Sánchez-Díez; Clara Gavira-O’Neill; Clara Gavira-O’Neill; Andrés J. García-Díaz; Tomás Landete-Castillejos; Carmen Ramírez-Castillejo; Carmen Ramírez-Castillejo; et al. (Frontiers in Bioengineering and Biotechnology)
Growing antlers in deer contain bioactive compounds, most of which are proteins and peptides with effects on health, such as anticancer and regenerative properties. However, efficient extraction of these biomolecules while preserving their integrity remains a challenge. This study aimed to optimize the extraction of proteins from growing antlers through liquid removal methods, solvent selection, ratios, temperature, and extraction time. Lyophilization was identified as the optimal method for preserving protein integrity, particularly in biologically active regions. Among the tested solvents, water emerged as the most effective for protein extraction, achieving optimal results at a 1:10 w/v ratio with 1 hour of magnetic stirring at room temperature, although remains to be tested the anticancer effect of solvents different to water. Insulin-like growth factor 1 (IGF-1) was quantified as a key indicator of extraction efficiency, demonstrating that the optimized protocol effectively preserves this kind of bioactive protein. This methodology provides a robust framework for the extraction of proteins from growing antlers, paving the way for future applications in biomedical research.